1966
DOI: 10.2466/pr0.1966.18.3.801
|View full text |Cite
|
Sign up to set email alerts
|

Uncertain Responses on Multiple-Choice Examinations

Abstract: 100 students were asked to label item responses on two multiple-choice tests as sure, uncertain, and guess. The uncertain category was significantly different from the sure and guessed response categories, and from the theoretical chance expectancy level. This demonstrates that the basic assumption of the correction-for-errors scoring formula (that all wrong responses are pure guesses) penalizes the student by utilizing only those responses of which he feels certain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It is commonly found that the higher the level of confidence, the greater the probability of being correct. Reports of this type of test have been published by West (1923), Brinkmeier & Keys (1930), Granich (1931), Melbo (1933), Davis (1959) , Hammerton (1965), Little & Creaser (1966), Hanna & Owens (1973), Abu-Sayf (1975), Koriat (1975, 1976) and LaVigna (1977. It is also commonly found that, although there is a positive association between the expressed degree of confidence and the probability of being right, subjects are far from perfect in their expressions of their state of k n o w l e d g e among the responses marked with complete confidence are some that are wrong, and among those marked as being complete guesses a higher-than-chance proportion are correct.…”
Section: Confidence Rating Of Selected Alternativesmentioning
confidence: 99%
“…It is commonly found that the higher the level of confidence, the greater the probability of being correct. Reports of this type of test have been published by West (1923), Brinkmeier & Keys (1930), Granich (1931), Melbo (1933), Davis (1959) , Hammerton (1965), Little & Creaser (1966), Hanna & Owens (1973), Abu-Sayf (1975), Koriat (1975, 1976) and LaVigna (1977. It is also commonly found that, although there is a positive association between the expressed degree of confidence and the probability of being right, subjects are far from perfect in their expressions of their state of k n o w l e d g e among the responses marked with complete confidence are some that are wrong, and among those marked as being complete guesses a higher-than-chance proportion are correct.…”
Section: Confidence Rating Of Selected Alternativesmentioning
confidence: 99%
“…We are testing to measure cognitive achievement; researchers (Sherriffs & Boomer, 1954; Votaw, 1936) have obtained data indicating that test constructors who discourage guessing introduce irrelevant personality factors that contaminate the test results. Furthermore, it has been shown (Little & Creaser, 1966) that the penalty for guessing formula overcorrects for misinformation and under‐corrects for partial information. This is important because it demonstates that formula scoring does not satisfy the assumptions of the examinee either fully knowing the answer to an item, or not knowing the correct answer at all and guessing totally at random.…”
Section: Encouraging Guessing On Multiple True‐false Questionsmentioning
confidence: 99%